Review Artikel : Evaluasi Hasil Pembentukan Senyawa Kompleks Inklusi Siklodekstrin Untuk Meningkatkan Kelarutan Di Dalam Air - Rismawanti, Rusi; Jafar, Garnadi; Herni Kusriani, R. (JURNAL FARMASI GALENIKA, 2023)
Cyclodextrin is one of the compounds that can increase the solubility of a compound in water by forming inclusion complexes. Almost 70% of new drug candidates discovered recently are compounds that have poor solubility in water, so many researchers are conducting research using cyclodextrin as one of the developments in improving compounds in new drug discovery. However, the results of this complex formation must still be reviewed by researchers, whether the inclusion complex formed has succeeded in changing a compound into water soluble, and stable during its application. This article review summarizes the explanation of the evaluation of the results of the formation of cyclodextrin inclusion complexes with several water-insoluble compounds by searching scientific journals that have been published nationally and internationally in the last 10 (ten) years from 2013-2023 through the google scholar database, Pubchem, and Science Direct. Evaluation of the results of cyclodextrin inclusion complex formation can be done by several methods both computationally and laboratory testing.